2005
DOI: 10.1111/j.1440-1746.2005.03749.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Barrett's esophagus in Korea

Abstract: Although the prevalence of BE in Korea appears to be lower than the reported rates from Western countries, it may not be as low as was previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 25 publications
(28 reference statements)
2
70
0
Order By: Relevance
“…The first multicenter prospective study for LSBE was conducted on 1,553 patients at five referral hospitals in Seoul, and the prevalence of BE was 0.3% [22]. After 2 years, the prevalence of SSBE was assessed prospectively in four referral hospitals of Seoul and the metropolitan areas on 992 patients; CLE was found in 108 patients (10.9%), the overall prevalence of SIM was 3.6%, and only three patients had LSBE [23]. In a single-center study of 70,103 patients given upper endoscopies, 696 (1%) patients had CLE, and BE was present in 151 patients (0.22%) [24].…”
Section: Discussionmentioning
confidence: 99%
“…The first multicenter prospective study for LSBE was conducted on 1,553 patients at five referral hospitals in Seoul, and the prevalence of BE was 0.3% [22]. After 2 years, the prevalence of SSBE was assessed prospectively in four referral hospitals of Seoul and the metropolitan areas on 992 patients; CLE was found in 108 patients (10.9%), the overall prevalence of SIM was 3.6%, and only three patients had LSBE [23]. In a single-center study of 70,103 patients given upper endoscopies, 696 (1%) patients had CLE, and BE was present in 151 patients (0.22%) [24].…”
Section: Discussionmentioning
confidence: 99%
“…32 The prevalence of BE was lower in women than in men (Table). 7,19,[40][41][42][43][44][45][46][47][48][49][50][51] A systematic review after analyzing the PubMed database between 1997 and 2011 has shown that the prevalence of BE was lower in women than in men (28 out of 10 337, range 0.03-4.6% vs 70 out of 12 463, range 0.08-8.2%).…”
Section: Prevalence Of Barrett's Esophagusmentioning
confidence: 99%
“…Although total gastrectomy and Roux-en Y procedure is a common procedure in Korea because of high incidence of gastric carcinoma, development of BE in these patients is not reported yet. This may be due to lower prevalence of BE in Korea than Western countries, 16 and low awareness of BE by endoscopists during follow up. Therefore, careful follow-up and endoscopic examination is required, since recurrent carcinoma after total gastrectomy has a chance to be adenocarcinoma associated with BE.…”
mentioning
confidence: 88%